'A transforming sentiment in this country': The Whitlam government and Indigenous self‐determination. Issue 1 (7th December 2018) - Hocking, Jenny
Abstract: Gough Whitlam's Labor government came to office in December 1972 with a vast and transformative reform agenda, at the heart of which was a fundamental policy shift in Aboriginal affairs away from assimilation and toward self‐determination, described by Whitlam as; 'Aboriginal communities deciding the pace and nature of their future development as significant components within a diverse Australia'. Whitlam's commitment to self‐determination reflected the United Nation's International Covenant on Civil and Political Rights, which refers to the right of all peoples to 'freely determine their political status and freely pursue their economic, social and cultural development'. Whitlam made it clear that Aboriginal Affairs would be a priority of his government with the establishment of the first separate Ministry for Aboriginal Affairs and his government introduced a suite of path‐breaking policies for Aboriginal people. Pat Dodson, the inaugural chairperson of the Council for Aboriginal Reconciliation, later described the change in policy and intent under Whitlam as, 'a transforming sentiment in this country for Aboriginal people'. This article explores the key features of Whitlam's Indigenous policy and argues that Whitlam's commitment to self‐determination was a unique and radical policy reframing in Indigenous affairs not seen before or since. These advances were wound back by the conservative government of Malcolm Fraser and the 'transforming sentiment' soon reverted to one of 'self‐management' and unarticulated assimilation. Abstract : This article explores the key elements of the Whitlam government's commitment to self‐determination, described as 'Aboriginal communities deciding the pace and nature of their future development', as the defining feature in Indigenous policy. The paper argues that Indigenous self‐determination was a unique policy reframing specific to the Whitlam government which was rapidly over‐turned by the Fraser conservative government.